2020
DOI: 10.3389/fonc.2020.00718
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genetic Alteration Signatures and Prognostic Values of m6A Regulatory Genes in Head and Neck Squamous Cell Carcinoma

Abstract: Genetic alteration involving N6-methyladenosine (m6A) regulatory genes is a frequent characteristic of multiple tumors. Nevertheless, little is known regarding their genetic alteration signatures and prognostic values in head and neck squamous cell carcinoma (HNSCC). In this study, RNA sequence profiles and copy number variation (CNV) data of 506 HNSCC patients were downloaded from The Cancer Genome Atlas (TCGA) database. Correlation analysis involving alteration of m6A regulatory genes, clinicopathological ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 35 publications
3
39
0
Order By: Relevance
“…ALKBH5 can regulate the malignant behaviour of breast cancer, gastric cancer and glioblastoma 32,33 . ALKBH5 and YTHDC2 were independent risk factors for OS of head and neck squamous cell carcinoma 34 . ZC3H13 can suppress the proliferation and invasion of colorectal cancer cells 35 .…”
Section: Discussionmentioning
confidence: 99%
“…ALKBH5 can regulate the malignant behaviour of breast cancer, gastric cancer and glioblastoma 32,33 . ALKBH5 and YTHDC2 were independent risk factors for OS of head and neck squamous cell carcinoma 34 . ZC3H13 can suppress the proliferation and invasion of colorectal cancer cells 35 .…”
Section: Discussionmentioning
confidence: 99%
“…YTHDC2 can improve the efficiency of the translation and reduce the abundance of mRNA through its helicase and can improve the efficiency of HIF-1 α mRNA translation ( Tanabe et al., 2016 ), and can adjust the happening of the sperm ( Hsu et al., 2017 ). Recent studies have shown that low expression of YTHDC2 was associated with poor prognosis and correlated with activation of apoptosis and ubiquitin-mediated proteolysis in HNSCC ( Zhou et al., 2020 ). Besides, Zhao & Cui (2019) also found that two m6A methylation “readers”—YTHDC2 and heterogeneous nuclear ribonucleoprotein C (HNRNPC) could construct a prognostic signature and predict the survival time in HNSCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…For example, HNSCC therapy has undergone a significant change in recent years with the development of precision medicines, such as bevacizumab, against vascular endothelial growth factor (VEGF)/VEGF receptor (VEGFR) based on the special gene expression signature, and prognostic outcomes in HNSCC (3)(4)(5). More recently, increasing knowledge has brought into focus the features of several macromolecules (protein, RNA, DNA, and sugar) that are involved in tumorigenesis and progression, especially in epigenetic modifications; and the value of these features as prognostic indicators and potential therapeutic targets has been gradually recognized (6)(7)(8). To date, the molecular mechanism of HNSCC occurrence and development has not yet been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, RNA methylation predominantly includes m 6 A, m 5 C, m 1 A, and m 7 G, among which m 6 A and m 5 C modification techniques are two of the most major and most representative types of posttranscriptional RNA modification in over 170 chemical modification schemes (12)(13)(14)(15). The m 6 A modification technique has been predominantly studied in HNSCC, but that of m 5 C does not attract much attention since the current knowledge of its functions is limited to regulation of the exportation of mRNA and the maintenance of the structure and stability of mRNA (12,(16)(17)(18). Its modulating effects have been characterized to be reversible and dynamic, similar to those of histone and DNA modification methods, owing to the involvement of m 5 C writers, erasers, and readers (19,20).…”
Section: Introductionmentioning
confidence: 99%